DEVELOP QUALITY PEOPLE THROUGH DA’WAH IN THE FACE OF THE ASEAN ECONOMIC COMMUNITY (AEC) - Mubasyaroh, Mubasyaroh (ADDIN, 2016)
Recent decades, we often hear the advent of the Asean Economic Community (AEC) which is a community that is struggling in the field of free market economies in particular, so it requires some readiness; economic, capital, and the equally important need readiness of human resources as the party who run the economy. For Indonesia alone, MEA will be an opportunity for trade barriers will tend to diminish even be non-existent. This will impact on increasing exports, which in turn will increase the GDP of Indonesia. On the other hand, the Muslims as the vast majority of Indonesia's population must face the Asean Economic Community (AEC). In this case Indonesian Muslims should be careful and ready to face the AEC. Campaigners Indonesian economy began to prepare for the era of free markets that will be enforced. The era of the free market itself is the result of the formation of the Asean Economic Community (AEC). The free market itself covering the areas of capital, goods and services, and labor. In this regard, please note that the mission is a process conducted by a conscious and planned to invite the people to the path of Allah, to improve the situation for the better (da’wah is the promotion and development) in order to achieve certain goals, namely to live happily in the world hereafter. In this paper will attempt to peel da’wah efforts in developing the quality of the people in the face of the Asean Economic Community (AEC).